1996
DOI: 10.1101/gad.10.17.2189
|View full text |Cite
|
Sign up to set email alerts
|

The Caenorhabditis elegans gene lin-17, which is required for certain asymmetric cell divisions, encodes a putative seven-transmembrane protein similar to the Drosophila frizzled protein.

Abstract: Mutations in the gene lin-1 7 result in the disruption of a variety of asymmetric cell divisions in Caenorhabditis elegans. We have found that lin-1 7 encodes a protein with seven putative transmembrane domains. The LIN-17 protein is most similar to the Drosophila Frizzled protein and its vertebrate homologs. Studies using a lin-1 7-green fluorescent protein translational fusion indicate that lin-1 7 is expressed in mother cells before asymmetric cell divisions and in both daughter cells after the divisions. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
125
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(131 citation statements)
references
References 50 publications
4
125
0
2
Order By: Relevance
“…We found that daf-1(m40) does not suppress the M lineage defects of sma-9(cc604) ( Table 4). Similarly,, mutations in the Wnt signaling pathway (Maloof et al, 1999;Sawa et al, 1996), do not suppress the M lineage defects of sma-9(cc604) (data not shown). These results indicate a specific role for SMA-9 in modulating the core Sma/Mab TGF␤ pathway in M lineage patterning.…”
Section: Research Articlementioning
confidence: 99%
“…We found that daf-1(m40) does not suppress the M lineage defects of sma-9(cc604) ( Table 4). Similarly,, mutations in the Wnt signaling pathway (Maloof et al, 1999;Sawa et al, 1996), do not suppress the M lineage defects of sma-9(cc604) (data not shown). These results indicate a specific role for SMA-9 in modulating the core Sma/Mab TGF␤ pathway in M lineage patterning.…”
Section: Research Articlementioning
confidence: 99%
“…lin-17 mutants have cell fate defects (Sawa et al, 1996). To address whether the PLM polarity defect results from a cell fate transformation, we examined expression of three PLM fate markers: mec-4::gfp, mec-7::gfp and mgl-2::gfp.…”
Section: Research Articlementioning
confidence: 99%
“…elegans has five Wnts [CWN-1, CWN-2, EGL-20, LIN-44 and MOM-2 (Shackleford et al, 1993;Herman et al, 1995;Thorpe et al, 1997;Whangbo and Kenyon, 1999)], four Frizzleds [CFZ-2, LIN-17, MIG-1 and MOM-5 (Sawa et al, 1996;Rocheleau et al, 1997;Zinovyeva and Forrester, 2005;Pan et al, 2006)] and a single Ryk, LIN-18 (Inoue et al, 2004). Wnt signaling establishes the polarity of asymmetric cell divisions, determines cell fates and guides cell migrations (Korswagen, 2002;Herman, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…elegans has four genes encoding Frizzled receptors, lin-17, mom-5, mig-1, and cfz-2 (Sawa et al 1996;Rocheleau et al 1997;Ruvkun and Hobert 1998;Zhao et al 2003), and a single Ryk/ Derailed receptor homolog encoded by lin-18 (Inoue et al 2004), which appear to function -14, mig-1, vps-35, cam-1(gf), egl-20, lin-17, mig-5, bar-1, pop-1, mab-5 Wild type QR.d QL.d as Wnt receptors. As with the Wnt ligands, for some processes the receptors display genetic redundancy such that Wnt reduction-of-function phenotypes are only seen when multiple genes are mutated (Gleason et al 2006;Pan et al 2006;Green et al 2008;Zinovyeva et al 2008).…”
Section: Wnt Receptors: No Coreceptor?mentioning
confidence: 99%